Logoreja u pesničkoj zbirci Branislava Petrovića Moć govora (Philologia, 2024)
In medical terminology, the word ”logorrhea” denotes a disorder of excessive and uncontrolled talking, while in everyday speech it is often used as a synonym for talkativeness or chatter. In this paper, we have tried to indicate the meaning of the logorrheic principle in Branislav Petrovic’s first poetry collection. Given that the term was also used in ancient philosophy to denote the speech of matter, which only sages can hear, we have determined whether Petrovic privileges the position of the poet by using the principle of logorrhea. The author shapes the poetic speech as a free associative verbal flow, with numerous neologisms and repetitions, forming strange morphosyntactic constructions, whereby formal inventiveness is accompanied by numerous metalinguistic assumptions.
Keywords: Branislav Petrovic; The Power of Speech; logorrhea; speech; poetic language; language function; repetition; creation